Development of Animated Video Media Using Adobe Animate and Canva for Fourth Grade Pancasila Education - Wulan Rahmadania; Etri Wahyuni; Yesi Anita; Gita Rahmi (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
This study was motivated by the limited use of digital learning media in fourth-grade elementary school Pancasila Education learning, causing students to be less active, less focused, and less interested during the learning process. Therefore, a collaborative animated video learning media based on Web Adobe Animate and Canva was developed. This study aimed to produce learning media that are valid, practical, and effective for fourth-grade elementary school students. The research employed a Research and Development (R&D) method using the Plomp development model, which consists of three phases: preliminary research, prototyping phase, and assessment phase. The research subjects were fourth-grade students at SDN 11 Ampang. Data were collected through interviews, questionnaires, observation sheets, and learning outcome tests. The results showed that the media achieved a very valid category based on material, language, and media expert validation. The practicality test results indicated that the media was highly practical according to teachers’ and students’ responses. Furthermore, the effectiveness test using N-Gain obtained a score of 0.7653 (76.52%) categorized as effective. Therefore, the collaborative animated video learning media developed is feasible for use in Pendidikan Pancasila learning in elementary schools.